The importance of relationships for the produced knowledge in the sector of management consulting - Lopes da Costa, R.; Tavares, F.; Miguel, M (Journal of Management Research, 2013)
While the management consulting industry has been largely linked to the knowledge produced within the disciplines of strategic management in the academic field, the truth is that very little literature is produced in terms of research in this area, while the researchers focused more on a set of static techniques to be applied in the development of this field of research concerns. This article seeks to bridge this gap as well, showing by example that the consultancy sector is a true field of opportunities for the study of relationships management. This presentation is thus the aim of contributing both theoretically and empirically in the area of relationships through research in the context of management consulting, trying to visualize how the relationships are manifested in a context of high involvement and personal contact, and what’s the perception that must be taken into consideration by clients and consultants in terms of the benefits of their greater or lesser degree of involvement.